Validity of Serum Uromodulin as Early Diagnosis Marker of Diabetic Nephropathy in T2DM - Dumpatna, Rizki; Tristina, Nina; Turbawaty, Dewi Kartika; Tjandrawati, Anna (Majalah Kedokteran Bandung, 2021)
Increased prevalence of DM is accompanied by increased in its various complications include diabetic nephropathy, which can lead to end stage renal disease (ESRD). Urinary albumin-creatinine ratio (uACR) is the gold standard for diabetic nephropathy; however, it has several limitations, including the inability to early diagnose due to the absence of increased level in uACR. Uromodulin is produced by thick ascending limb (TAL) at Henle’s loop and early distal tubule of nephron. Uromodulin will decrease when tubular atrophy occurs in early stage of renal impairment with normoalbuminuria. The aim of this study was to determine the validity of serum uromodulin in type 2 diabetes mellitus (T2DM) in identifying diabetic nephropathy by comparing it with uACR as gold standard. This study was a cross-sectional analytical observational study at Dr. Hasan Sadikin (RSHS) Bandung from June to August 2020. Subjects consisted of 62 patiens with T2DM. Results showed that the serum uromodulin level had a sensitivity of 93.3%, a specificity of 88.2%, a positive predictive value of 95.5%, a negative predictive value of 83.3%, and an accuracy of 91,9% and an AUC value of 0.975. The cut-off point of serum uromodulin in this study was 47.195 ng/mL. In conclusion, serum uromodulin, when compared to the uACR as the gold standard, has good sensitivity and specificity for identifying diabetic nephropathy.